Kontribusi Penerimaan Pajak Bumi dan Bangunan Pada Pendapatan Asli Daerah - Febriyanto, Dimas; Khasanah, Uswatun (Rifa'Institute, 2023)
This study aims to analyze how big is the contribution of Land and Building Tax to Regional Original Income in Bekasi Regency, where Land and Building Tax is a potential source of local revenue as a source of financing for government activities in Bekasi Regency as well as regional development and economy. The method used in this research is interview with direct communication techniques either directly or indirectly. Data collection in this qualitative research was collected primary data and secondary data. Primary data through observation and interviews with BAPENDA officials who are directly involved with the collection of Land and Building Tax in Bekasi Regency which is used as information to obtain verbal information regarding their understanding, opinion and involvement in tax collection.